2012
DOI: 10.3109/01676830.2011.639477
|View full text |Cite
|
Sign up to set email alerts
|

Enucleation and Evisceration: 20 Years of Experience

Abstract: Evisceration was found to be a safe and quicker alternative to enucleation in our study. A change in surgical preference from enucleation to evisceration was seen during the 20-year study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 10 publications
3
43
3
4
Order By: Relevance
“…2) was performed most commonly ( P = 0.033). Similar findings were also reported in other series 3,16. Exenteration (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…2) was performed most commonly ( P = 0.033). Similar findings were also reported in other series 3,16. Exenteration (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The differences between procedures based on sex may reflect the cumulative effect of sex distribution and preferred eye removal technique for each pathologic indication. A global trend toward eviscerations has been noted in numerous studies, 5,10,12,28,46 the benefits of which may include improved tissue preservation and cosmetic results, faster recovery, and motility of the prosthetic implant with a low complication rate. 5,10,12,47,48 In cases of suspected neoplasms that cannot be treated with eye-sparing treatments, enucleation is preferred over evisceration.…”
Section: Discussionmentioning
confidence: 99%
“…4 Evisceration may provide better implant motility for the prosthetic eye and may improve cosmetic outcomes. 5 Exenteration is typically reserved for cases of extensive tumour invasion of the orbit 6 or where aggressive treatment is necessary.…”
mentioning
confidence: 99%
“…Overall, 83.4% of the surgeries were enucleation, 13.4% were evisceration, and 3.2% were exantration, which is consistent with the previous reports. [357] Contradicting this, other studies have reported evisceration as the major surgical approach. [89]…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from Nigeria, the most prevalent clinical indication of eye surgeries was reported to be infectious causes such as perforated corneal ulcer, endophthalmitis and panophthalmitis (32.1%), trauma (21.2%), and tumors (21.2%), while the most prevalent indication of eye enucleation in children was reported to be retinoblastoma,[2] while several other studies have reported trauma[134] or tumors[5] as the most prevalent cause of enucleation. Often the psychological effects of losing eyes are much worse than its physical problems, especially in cases of losing eyes due to trauma or unexpected malignancy.…”
Section: Introductionmentioning
confidence: 99%